Communicating effectively - Hybels, Saundra (McGraw-Hill, 2009)
This text presents the foundation of communication studies through numerous examples that range from the campus to the workplace to communities both in the United States and throughout the world. Every chapter contains numerous activities that engage students and promote group work. This edition has a new section, the Reality Check, which challenges students to think more deeply and practically about the ideas, concepts, and approaches they encounter and to apply them to their lives